Burma Displaced - Wehap, Roland (Austria, 2010)
"Burma Displaced" follows the Burmese people who were able to flee Burma during the Saffron Revolution 2007 and the hurricane Nargis. They live as illegal workers in neighbouring countries, in refugee camps in Bangladesh, as tourist attraction in Thailand and lonely in the Swiss mountains. The film also meets the Rap Group "Myanmar Future Generation" who sings about Burma's horrible history. The film finds destroyed villages and fleeing people. The one thing they all have in common is hope: Hope for a better live, hope for a freed Burma.
Verzio Film Festival Submission
Keywords: Documentary films